Social network bridging potential and the use of complementary and alternative medicine in later life. (September 2015) - Goldman, Alyssa W.; Cornwell, Benjamin
Abstract: The use of complementary/alternative medicine (CAM) is typically modeled as a function of individual health beliefs, including changes in perceptions of conventional medicine, an orientation toward more holistic care, and increasing patient involvement in health care decision-making. Expanding on research that shows that health-related behavior is shaped by social networks, this paper examines the possibility that CAM usage is partly a function of individuals' social network structure. We argue that people are more likely to adopt CAM when they function as bridges between network members who are otherwise not (or poorly) connected to each other. This circumstance not only provides individuals with access to a wider range of information about treatment options, it also reduces the risk of sanctioning by network members if one deviates from conventional forms of treatment. We test this idea using data from the National Social Life, Health, and Aging Project (NSHAP), a nationally representative study of older Americans. Analyses of egocentric social network data show that older adults with bridging potential in their networks are significantly more likely to engage in a greater number of types of CAM. We close by discussing alternative explanations of these findings and their potential implications for research on CAM usage. Highlights: Study examines CAM usage and social network structure among American older adults. We model CAM usage as a function of social network bridging potential. Bridging potential may provide individuals with greater access to novel information and reduce the risk of social sanctioning. Social network bridging potential predicts a greater number of CAM practices used. Predicted CAM usage among bridges is nearly 40% greater than that of non-bridges.